ANALYSIS OF THE RELATIONSHIP BETWEEN COMPRESSIVE STRENGTH AND BENDING STRENGTH OF CONCRETE WITH FC 30 MEGAPASCAL (MPA) - Budiarto, Rika; Azhar, Moh; Bangun, Sempurna; Naibaho, Pio Ranap Tua (University Muhammadiyah Jakarta, 2024)
With the rapid development in the field of construction, various material innovations are increasingly emerging, especially in concrete. Concrete is in high demand for its durability, resistance to pressure, and low maintenance costs. Made from a growing mix of cement, coarse aggregate (split), fine aggregate (sand), water, and additives, concrete is becoming a top choice in modern infrastructure. This study aims to explore the relationship between compressive strength and flexural strength in 30 MPa quality concrete. The method used was a laboratory experiment with cylindrical and block-shaped test pieces, which were tested at the ages of 7, 14, and 28 days. The main materials used include coarse and fine aggregates, water, fly ash, and Portland type I cement. The study measured the compressive strength values of concreate, and evaluated the formula \(fs=0.62√(fc^' ) \) as stated in SNI 2847:2013 to test its relevance to this quality concrete. The results showed that the flexural strength increased with the age of the concrete, with the largest difference between compressive strength and flexural strength at 1.3%. These findings support a deeper understanding of the performance of concrete at a given age and the relevance of the standard formula for 30 MPa quality concrete.